Blastocyst formation, embryo transfer and breed comparison in the first reported large scale cloning of camels - P. O. Olsson (Nature Portfolio, 2021)
Abstract Cloning, through somatic cell nuclear transfer (SCNT), has the potential for a large expansion of genetically favorable traits in a population in a relatively short term. In the present study we aimed to produce multiple cloned camels from racing, show and dairy exemplars. We compared several parameters including oocyte source, donor cell and breed differences, transfer methods, embryo formation and pregnancy rates and maintenance following SCNT. We successfully achieved 47 pregnancies, 28 births and 19 cloned offspring who are at present healthy and have developed normally. Here we report cloned camels from surgical embryo transfer and correlate blastocyst formation rates with the ability to achieve pregnancies. We found no difference in the parameters affecting production of clones by camel breed, and show clear differences on oocyte source in cloning outcomes. Taken together we demonstrate that large scale cloning of camels is possible and that further improvements can be achieved.